(untitled) (Marketing Journal, 2026)
Abstract This article analyzes the role of e-commerce and online trade in the modern economy, as well as the trends and prospects for their development. The study examines the impact of e-commerce on entrepreneurial activity, the importance of digital technologies in trade processes, and the key factors influencing the development of online trade in Uzbekistan. The research provides a scientific justification of the economic efficiency of e-commerce and identifies current challenges in this field. Keywords: e-commerce, online trade, digital economy, internet technologies, electronic payment systems, entrepreneurship.